Gender equity and trichiasis surgery in the Vietnam and Tanzania national trachoma control programmes. Issue 11 (15th October 2004) - West, S; Nguyen, M Phuong; Mkocha, H; Holdsworth, G; Ngirwamungu, E; Kilima, P; Munoz, B
Abstract : Aims: To calculate the gender distribution of trichiasis cases in trachoma communities in Vietnam and Tanzania, and the gender distribution of surgical cases, to determine if women are using surgical services proportional to their needs. Methods: Population based data from surveys done in Tanzania and Vietnam as part of the national trachoma control programmes were used to determine the rate of trichiasis by gender in the population. Surgical records provided data on the gender ratio of surgical cases. Results: The rates of trichiasis in both countries are from 1.4-fold to sixfold higher in females compared to males. In both countries, the female to male rate of surgery was the same or even higher than the female to male rate of trichiasis in the population. Conclusions: These data provide assurance of gender equity in the provision and use of trichiasis surgery services in the national programmes of these two countries. Such simple analyses should be used by other programmes to assure gender equity in provision and use of trichiasis surgery services.